Point-of-Sale System Architecture Design To Support the Digital Transformation of MSMEs (F&B) - Lily Damayanti; Andri Wijaya (Komunitas Dosen Indonesia, 2026)
The rapid development of information technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) in the Food and Beverage (F&B) sector to digitalize their business processes to improve efficiency and competitiveness. However, most existing Point-of-Sale (POS) solutions adopted by MSMEs remain fragmented and application-centric, focusing primarily on transaction processing while lacking architectural integration across business processes, data management, application services, and supporting technology infrastructure. This architectural gap limits system scalability, interoperability, and long-term alignment with MSME operational growth. This study aims to design an integrated POS system architecture that positions POS development as an architectural transformation framework rather than a standalone system implementation. A descriptive qualitative, problem-solving approach is employed, involving requirement identification from multiple F&B MSMEs, enterprise architecture modeling using the TOGAF Architecture Development Method (ADM), and iterative refinement through Agile development cycles. The proposed architecture integrates business, data, application, and technology domains, producing a cohesive architectural blueprint and traceable design artifacts adapted to MSME operational characteristics and resource constraints. System validation is conducted through User Acceptance Testing (UAT) involving MSME end users. The results indicate high usability and functional adequacy for core operational activities, including sales transactions, inventory control, reporting, and petty cash management. These findings suggest that the proposed architecture is practically feasible for real-world adoption and can serve as a scalable foundation for future digital integration. Overall, this study contributes a structured and adaptable POS architectural framework that enhances integration, digital readiness, and sustainable transformation in the F&B MSME sector.